Enhancing access to genetic resources for climate change adaptation in Kenya, Uganda and Tanzania: Seed catalogue of best performing varieties of beans and finger millet in Hoima Uganda - Otieno, Gloria Atieno; Recha, Tobias; Fadda, Carlo; Mulumba, John W.; Adokorach, Joyce; Ahumuza, Jasper; Kakeeto, Ronald; Kairagura, Godfrey (Bioversity International, 2020)
In Uganda, climate change, homogenization of agriculture to single crops or varieties coupled with the associated loss of biodiversity has decreased the resilience of resource-poor farmers and affected their food and nutrition security. The loss of genetic diversity in farmers’ custody has greatly narrowed the gene pool from which they depend on. In order to help them adapt to climate change, two projects: “Promoting Open Source Seed Systems for Beans, Millet and Sorghum for Climate Change Adaptation” funded by the Benefit-sharing Fund (BSF) of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) and “Citizen’s Science approach to climate-smart and nutrition-sensitive seed value chains for food and nutrition security in Uganda and Ethiopia”, funded by the Netherlands Organization for Scientific Research (NWO) were implemented in Uganda. Through these projects, farmers in Hoima Uganda tested and evaluated 34 beans and 44 finger millet varieties. They were able to select 7 beans and 7 finger millet varieties based on their preferred attributes like early maturity, pest and disease resistance, drought tolerance yield and taste. This catalogue presents the top selected varieties of beans and finger millet including their agronomic attributes and nutritional benefits. Varieties identified here are possible candidates for breeding.